Correlation of ECG changes at high altitude with findings on Coronary Angiogram. - Saif, Mohsin; Rahman, Fahd Ur; Liaqat, Jahanzeb; Sajid, Usman; Saeed, Farrukh; Khan, Aleena; Khan, Muhammad Nadir; Samore, Naseer Ahmed; Siddique, Muhammad Bilal; Arshad, Junaid (Pakistan Armed Forces Medical Journal, 2022)
Objective: To highlight association of coronary artery disease on angiograms and high altitude-related ECG abnormalities that is thought to be ischemic in origin.Place and Duration of Study: This was a cross sectional study done in Armed Force Institute of Cardiology/National Institute of Heart Disease from Oct 2016 to Oct 2021.Methodology: This was a cross sectional study done in AFIC/NIHD from Oct 2016–Oct 2021 (5years). A total of 103 patients at a range of 9000 to 22000 feet in altitude, with new ECG changes were selected via consecutive sampling. Data was analyzed by SPSS version-23. Descriptive statistics were run to present categorical data in frequencies and percentages. Chi-square and Fisher Exact Test was applied to find the association between study variables at 95% CI and 5% margin of error (α= 5%).Results: The data was collected from a total of 103 respondents, mean age (years) of the respondents was 30.57±6.27, and mean duration of stay (days) at high altitude was 64.8±68.3 (Table-I). ECG changes that were recorded were: T-wave inversion in anterior leads (V1, V2, V3) were reported in n=33(32%), T- wave inversion in Inferior leads (II, III, aVF) in 21(20.3%), T-wave inversion in lateral leads (V3-V6) 10(9.7%). Normal Ejection fraction was observed in 97% of the study participants while only 3% had mild left ventricular systolic impairment. Angiographic findings were found to be normal in n=92 (89.30%), minor coronary artery disease (CAD) in n=9 (8.70%), muscle bridge in LAD in n=2 (1.90%). Our results also showed that amongst other final diagnosis, of note were vasovagal syncope (n=5; 4.8%), pulmonary embolism (n=5; 4.8%) and pulmonary arterial hypertension (n=3; 2.9%).Conclusion: Our work leads us to the conclusion that ECG abnormalities at high altitude do not indicate coronary artery disease since they do not reflect a delay in electrical conduction or ischemia. These patients should be treated separately based on their high altitude disease symptoms (HAI).